Analisis Dimensi Kecerdasan Emosional Terhadap Komitmen Pengembangan Sociopreneur - Akbar, Syamsul; Yuliana, Ika; Marlina , Febria Nurmelia; Cahyadi, Irwan; Talidobel, Susilo (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to analyze the influence of emotional intelligence, which encompasses self-awareness, self-management, self-motivation, empathy, and social skills, on commitment to sociopreneurship development. The study employed a quantitative approach with a causal design, involving 80 sociopreneurs from the Coconut Processing Industry Center in Pemenang Regency. Based on the data analysis, it was found that three aspects of emotional intelligence self-motivation, empathy, and social skills have a positive and significant influence on commitment to sociopreneurship development. Conversely, self-awareness and self-management did not significantly influence this commitment. These findings confirm that not all dimensions of emotional intelligence play an equal role in shaping a sociopreneur's commitment. Aspects such as self-motivation, empathy, and social skills have been shown to be more influential in encouraging individuals to remain committed to their social roles. The implications of this research are the importance of training and developing emotional intelligence, particularly in enhancing intrinsic motivation, the ability to understand others, and social interaction skills. Development programs for sociopreneurs need to focus on strengthening these three aspects to foster long-term commitment that will impact business sustainability and achieve desired social goals. A strong commitment to sociopreneur development is crucial to supporting the sustainable achievement of social and economic goals, particularly in the context of community-based industries like coconut processing.